Gedung Jurusan Seni Musik Sekolah Tinggi Seni Riau Dengan Pendekatan Arsitektur Tropis - Diko Despabera Rosdianto; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Building of music major is facility and infrastructure academic activity in STSR (Sekolah Tinggi Seni Riau) in Pekanbaru, which uses curriculum standard for advanced art in accordance to government regulation. This STSR music building uses tropical architecture in order to answer various set of problems related to climate that influence the site. Some of the tropical architecture principals applied in the design are: (1) building orientation; (2) maximise natural airing; (3) wide green open space; (4) responsive towards surroundings. Melody in Art is the chosen concept to answer various set of problems that appeared along designing process. This concept is applied in every architectural aspect of designing, such as; mass arrangement, mass shape/form, landscape, and building façade. Mass arrangement determines the public zone, semi-public, and private, spherical form and rectangle are transformed, interesting landscape arrangement composes musical score and facade is suited with surroundings. These explanations are the concept application of designing. This STSR music building has six masses and every mass has tilted roof to respond the climate, some masses have ventilation in order to let the air through inside the building, sun shading and overhand are used in every mass in order to minimize sun lighting into the building.Key Word: Building of music major ,Sekolah Tinggi Seni Riau, Tropical Architecture, Melody in Art.